Policy content and stakeholder network analysis for infant and young child feeding in Bangladesh - Sabrina Rasheed; Swapan Kumar Roy; Susmita Das; Syeda Nafisa Chowdhury; Mohammad Iqbal; Syeda Mahsina Akter; Khurshid Jahan; Shahadat Uddin; Anne Marie Thow (BMC, 2017)
Abstract Background Appropriate infant and young child feeding (IYCF) practices are essential for nutrition of infants and young children. Bangladesh has one of the highest levels of malnutrition globally along with sub-optimal IYCF practices. A supportive policy environment is essential to ensure that effective IYCF interventions are scaled up. The objectives of our study were to assess the support for IYCF in the national policy environment through policy analysis and stakeholder analysis and in so doing identify opportunities to strengthen the policy environment. Methods We used a matrix developed by SAIFRN (the South Asian Infant Feeding Research Network) to systematically identify supportive national policies, plans and guidelines for IYCF. We adapted narrative synthesis and descriptive approaches to analyze policy content, based on four themes with a focus on support for mothers. We conducted three Net-Map interviews to identify stakeholders who influenced the policies and programs related to IYCF. Results We identified 19 national policy documents relevant to IYCF. Overall, there was good level of support for IYCF practices at policy level - particularly regarding general support for IYCF and provision of information to mothers - but these were not consistently supported at implementation level, particularly regarding specificity and population coverage. We identified gaps regarding the training of health workers, capacity building, the monitoring and targeting of vulnerable mothers and providing an enabling environment to mothers, specifically with respect to maternity leave for working women. Urban populations and providers outside the public sector remained uncovered by policy. Our stakeholder analysis identified government entities such as the National Nutrition Service, as the most influential in terms of both technical and funding support as they had the mandate for formulation and implementation of policies and national programs. Stakeholders from different sectors played important roles, demonstrating the salience of IYCF. Conclusions Although there is strong supportive policy environment for IYCF, it is important that policies cover all populations. Our analysis indicated that opportunities to strengthen the policy environment include: expanding population coverage, increasing inter-sector coordination, improving translation of policy objectives to implementation-level documents, and the engagement of non-public sectors. In addition, we recommend explicit strategies to engage diverse stakeholders in the formulation and implementation of IYCF policies.